Pengaruh Sumber Daya Manusia, Permodalan dan Pemasaran Terhadap Kinerja Usaha Kecil dan Menengah Sari Apel di Kecamatan Tutur - Muhammad Nizar (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
This article aims to determine the effect of Human Resources, Capital and Marketing Against Small and Medium Business Performance of Apple Cider. And find out how much influence Human Resources, Capital and Marketing Against Small and Medium Business Performance Apple cider. The population in this article is Small and Medium Business of Apple Cider located in Tutur District, while the sample used is 35 people consisting of the owner of Small and Medium Business Owner of Apple Cider and analyzed by using multiple regression analysis. The data and used in this article are primary and secondary data.